2013
DOI: 10.3892/ijo.2013.1818
|View full text |Cite
|
Sign up to set email alerts
|

Ratio disruption of the Δ133p53 and TAp53 isoform equilibrium correlates with poor clinical outcome in intrahepatic cholangiocarcinoma

Abstract: Abstract. All p53 family members are expressed in several isoforms through alternative promoters and alternative splicing. However, the significance of these isoforms is not yet well understood in cholangiocarcinoma (CCA). In this study, we investigated the expression of p53, p63, p73 and their isoforms at the mRNA and protein levels in CCA. The overexpression of ∆133p53 was observed in the CCA cell lines and clinical specimens. Moreover, the high expression of ∆133p53/TAp53 correlated with short overall survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 19 publications
3
39
2
Order By: Relevance
“…Based on the observation that different p53 isoforms can be differentially expressed in tumors compared with normal tissue, an importance of alternative isoforms in carcinogenesis became clear [174,175,176]. For example, abnormal expression of p53 isoforms was reported in acute myeloid leukemia (AML), cholangiocarcinoma, colon carcinoma, glioblastoma, head and neck tumors, lung tumors, and ovarian tumors [177,178,179,180,181,182]. It was shown that normal breast tissue expresss p53α, p53β, and p53γ, whereas the expression of p53β and p53γ is lost in 60% of breast tumors, which instead frequently overexpress the isoform Δ133p53 [183].…”
Section: Inducible/modified Proteoforms Of P53mentioning
confidence: 99%
“…Based on the observation that different p53 isoforms can be differentially expressed in tumors compared with normal tissue, an importance of alternative isoforms in carcinogenesis became clear [174,175,176]. For example, abnormal expression of p53 isoforms was reported in acute myeloid leukemia (AML), cholangiocarcinoma, colon carcinoma, glioblastoma, head and neck tumors, lung tumors, and ovarian tumors [177,178,179,180,181,182]. It was shown that normal breast tissue expresss p53α, p53β, and p53γ, whereas the expression of p53β and p53γ is lost in 60% of breast tumors, which instead frequently overexpress the isoform Δ133p53 [183].…”
Section: Inducible/modified Proteoforms Of P53mentioning
confidence: 99%
“…In renal cell carcinoma (RCC), p53β and Δ133p53 isoforms are overexpressed in tumor cells compared with normal cells 77. Other studies have shown that p53 isoforms are also abnormally expressed in AML, cholangiocarcinoma, glioblastoma, head and neck tumors, colon carcinoma, and ovarian and lung tumors,7883 and it can be expected that numerous other types of cancer are concerned.…”
Section: Role Of P53 Isoforms In Human Cancer and Other Pathologiesmentioning
confidence: 99%
“…Indeed, mutant p53 breast patients expressing p53γ have as good a prognosis as WT p53 breast cancer patients, while mutant p53 breast cancer patients not expressing p53γ have a particularly poor prognosis, and would benefit from additional treatment 75. In cholangiocarcinoma, Δ133p53 overexpression is associated with a shortened overall survival 83. In acute myeloid leukemia, determination of p53 isoform expression revealed distinct p53 protein biosignatures correlating with clinical outcome 81,99…”
Section: Overview Of the Clinical Implications Of P53 Isoform Activitmentioning
confidence: 99%
“…Multiple studies have now shown that p53 isoforms have distinct functions and frequently contribute to diseases including cancer (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Elevated expression of the D40p53 isoform has been associated with metastatic melanoma and triple-negative breast cancers (7,19).…”
Section: Introductionmentioning
confidence: 99%